THE ANALYSIS OF POTENTIAL FRAUD AGAINST FINANCIAL STATEMENTS WITH DISCLOSURE REQUIREMENT AND IMPLICATIONS OF TAXATION - Ismail, Muhammad Nur (TEKUN: Jurnal Telaah Akuntansi dan Bisnis, 2019)
As a broad legal concept, fraud describes any deliberate fraudulent effort, which is intended to take the property or rights of another person or party. In the context of the audit of the financial statements as a deliberate misstatement. Taxation is very closely related to accounting. Basically, taxes are levied on economic activities of the company. Meanwhile, in charge of the accounting reports of economic activities in the framework of accountability to stakeholders. While the system of taxation which emphasizes trust to the taxpayer. This study focuses on the comparison between the financial statements for the particular income tax purposes compared with disclosure requirement and to determine the impact of taxation, formulate and analyze related research. The analysis of this study uses descriptive method that uses qualitative methods to examine the data in the form of information, the theory of the research library, and then by analyzing the data to resolve the case is formed, so that it can be deduced and advice can be given. The results of this study can be concluded there is potential fraudulent financial reporting in particular for corporate income tax reporting purposes look at the difference with disclosure requirement. This is because the management company did particularly VAT equalization tax on turnover in the corporate income tax by making various adjustments journal accounts in estimates related to income. The impact of taxation which is other than there is a lack of tax to be paid also added administrative sanctions such as penalty interest of 2% per month (maximum 48%) and a 50% penalty tax underpayments